SAUDI WOMEN AS AGENT OF CULTURAL SUSTAINABLE TRANSFORMATION THROUGH SUSTAINABLE DEVELOPMENT APPROACH: A QUALITATIVE STUDY - Abrar Alhomaid, (PEOPLE: International Journal of Social Sciences, 2025)
This research aims to identify the role of Saudi women in cultural sustainability as an aspect that generates and facilitates transformation towards sustainable development. The research is carried out in order to identify some directives which can reinforce the women’s position in the Saudi context according to the needs of vision 2030. It will examine how women can be considered as an agent of cultural sustainability to generate and facilitate transformation for a successful process for sustainable development. To reinforce this idea, this report will discuss the role of women on the social, economic and environmental transformation according to the requirement of a sustainable paradigm. As an explorative and descriptive approach, the research will adopt interviews to collect data. At all 25 interviews were conducted and a thematic analysis was operated by Atlas ti 8. The findings demonstrate that women are aware of the necessity to change and can contribute positively to the cultural transformation while preserving the present culture capital. The thematic analysis elaborated is used to dress a theorical model or a roadmap for a feminist cultural approach of sustainable development (economic, social and ecologic).